Relationship Between Missmatch Repair Protein Expression and Clinicopathological Features of Colorectal Cancer Patients - Muliani, Muliani; Bakri, Syakib; Luthfi Parewangi, Muhammad; Seweng, Arifin; Aman, Andi Makbul; Minhajat, Rahmawati (Asian Pacific Journal of Cancer Biology, 2025)
Background: The expression of Mismatch Repair (MMR) genes is a crucial mechanism in the pathogenesis of Colorectal Cancer (CRC). Clinicopathological characteristics stratified by MMR status can guide appropriate therapeutic strategies for patients. This study aimed to systematically review the relationship between clinicopathological characteristics and MMR status in CRC patients. Methods: A literature review was conducted, searching the PubMed, ScienceDirect, and Google Scholar databases for retrospective studies published within the last five years. The search strategy utilized a combination of keywords: ("Microsatellite Instability" OR "Gene Mutation" OR "Mismatch Repair") AND ("Colorectal Cancer" AND "Clinicopathology"). Relevant retrospective articles were selected for analysis. Results: A total of eight retrospective studies were included in this review. Consistently, tumors in patients with deficient MMR (dMMR) CRC exhibited larger sizes compared to those with proficient MMR (pMMR). No significant association was found between the total number of lymph nodes and MMR status. Inconsistent findings were reported regarding the association between MMR status and histological type, differentiation grade, tumor location, lymphovascular invasion (LVI), tumor stage, and lymph node metastasis. Despite these inconsistencies, the overall profile indicates that dMMR CRC is often associated with adverse histological features (e.g., poor differentiation and LVI) yet paradoxically presents at an earlier stage with low metastatic potential. Conclusio:n CRC with dMMR status presents a paradoxical clinicopathological profile. It is often histologically aggressive yet frequently localized, leading to a better prognosis in non-metastatic stages. A thorough understanding of these characteristics is essential for accurate risk stratification and for tailoring therapeutic strategies for patients with CRC.